Stakeholder Management Capability: A Discourse–Theoretical Approach - Zakhem, Abe (Journal of business ethics, 2008)
Since its inception, Stakeholder Management Capability (SMC) has constituted a powerful hermeneutic through which business organizations have understood and leveraged stakeholder relationships. On this model, achieving a high level of capability largely depends on managerial ability to effectively bargain with stakeholders and establish solidarity vis-à-vis the successful negotiation, implementation, and execution of "win–win" transactional exchanges. Against this account, it is rightly pointed out that a transactional explanation of stakeholder relationships, regarded by many as the bottom line for stakeholder management, fails to provide managerial direction regarding how to resolve a variety of normative stakeholder claims that resist commoditization. In response to this issue, this paper has two overlapping goals. It seeks to elaborate a discourse theoretical approach to the problem by first drawing out Jurgen Habermas’ theory of communicative action and delineating the various types of rational discourse. Second, the paper attempts to present concrete implications for SMC relative to reshaping the contours of rational, process, and transactional analysis in light of central discourse theoretical conclusions.